1991
DOI: 10.1128/jb.173.17.5546-5550.1991
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of phenolic catabolism in Rhizobium leguminosarum biovar trifolii

Abstract: In members of the family Rhizobiaceae, many phenolic compounds are degraded by the protocatechuate branch of the ,I-ketoadipate pathway. In this paper we describe a novel pattern of induction of protocatechuate (pca) genes in Rhizobium leguminosarum biovar trifolii. Isolation of pca mutant strains revealed that 4-hydroxybenzoate, quinate, and 4-coumarate are degraded via the protocatechuate pathway. At least three inducers govern catabolism of 4-hydroxybenzoate to succinyl coenzyme A and acetyl coenzyme A. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…A study of pca gene regulation in R. leguminosarum bv. trifolii found that the transferase (PcaIJ) was induced by ␤-ketoadipate or its CoA derivative (39). In A. tumefaciens A348 as well, adipate, a nonmetabolizable analog of ␤-ketoadipate (36), induced PcaIJ, but not PcaB (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of pca gene regulation in R. leguminosarum bv. trifolii found that the transferase (PcaIJ) was induced by ␤-ketoadipate or its CoA derivative (39). In A. tumefaciens A348 as well, adipate, a nonmetabolizable analog of ␤-ketoadipate (36), induced PcaIJ, but not PcaB (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous genetic strategies have evolved to regulate the protocatechuate branch of the ␤-ketoadipate pathway in different microbes (24,38,39,48). Elucidation of the induction pattern in A. tumefaciens enables it to be compared with those of other species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step in the metabolism of these compounds involves their conversion into either protocatechuate or catechol, which is subsequently metabolized to tricarboxylic acid intermediates via the ␤-ketoadipate pathway (18). This metabolic pathway has been documented in many members of the family Rhizobiaceae (23,35,(38)(39)(40), suggesting that the ␤-ketoadipate pathway is important for the survival of these soil-dwelling microorganisms.Sinorhizobium meliloti is a gram-negative, soil-dwelling bacterium that participates in a symbiotic relationship with the legume alfalfa through the establishment of nitrogen-fixing root nodules. Enzymes involved in the protocatechuate branch of the ␤-ketoadipate pathway in S. meliloti are encoded within the pcaDCHGB and pcaIJF operons, which are subject to regulation by products encoded by pcaQ and pcaR, respectively (23).…”
mentioning
confidence: 99%
“…The first step in the metabolism of these compounds involves their conversion into either protocatechuate or catechol, which is subsequently metabolized to tricarboxylic acid intermediates via the ␤-ketoadipate pathway (18). This metabolic pathway has been documented in many members of the family Rhizobiaceae (23,35,(38)(39)(40), suggesting that the ␤-ketoadipate pathway is important for the survival of these soil-dwelling microorganisms.…”
mentioning
confidence: 99%